2000
DOI: 10.1046/j.1440-169x.2000.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from mitosis to meiosis: Morphology and expression of proliferating cell nuclear antigen (PCNA) and Dmc1 during newt spermatogenesis

Abstract: The conversion from mitosis to meiosis is a phenomenon specific to the cellular progenitors of gametes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…2) (Yazawa et al ., 2000a). The primary spermatogonial nuclei are lightly stained and the largest among the spermatogenic cells (Figs.…”
Section: Morphological Changes During Spermatogenesismentioning
confidence: 99%
“…2) (Yazawa et al ., 2000a). The primary spermatogonial nuclei are lightly stained and the largest among the spermatogenic cells (Figs.…”
Section: Morphological Changes During Spermatogenesismentioning
confidence: 99%
“…However, these two methods cannot be undertaken on material obtained postmortem (Blottner and Roelants, 1998). Other techniques use the immunohistochemical detection of specific antigens, such as nuclear antigen PCNA, Ki 67 and TPS (Blottner and Roelants, 1998;Klein et al, 2000;Yazawa et al, 2000), which are selectively expressed during defined stages of the cell cycle. Using these techniques, however, antibody and species specificity must be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yazawa et al (2000) revealed that the spermatogonial stage in the newt could be divided into the following two phases similar to that in Xenopus; early (the first to the fourth generations) and late (the fifth to the eighth generations) phases. In contrast with Xenopus secondary spermatogonia which are able to convert mitotic phase to meiotic phase after the merely five mitotic divisions, the newt spermatogonia usually do not enter the meiotic phase until the completion of the eight mitotic divisions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yazawa et al (2000) observed the features of mitotic divisions during the spermatogonial stage and showed that there were two kinds of mitotic phases. The nuclear diameter of spermatogonia progressively decreased after the division during early phase and then remained constant throughout late phase.…”
Section: Introductionmentioning
confidence: 99%